PENYUSUNAN BAHAN AJAR SIMULASI PERKANTORAN DIGITAL BERBASIS PROJECT BASED LEARNING - Nelly Armayanti; Dodi Pramana; M. Fitri Rahmadana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2024)
Professional teaching staff have a direct influence on student learning outcomes, especially in the 21st century, where developments in technology, information and communication are growing rapidly. The challenge of 21st century learning is a problem found in the office administration education study program, namely the lack of digital-based teaching materials owned by lecturers to teach these courses. This research aims to prepare teaching materials for the Theory and Practice based Office Simulation course and is also accompanied by a Project Based Learning model. The reason for choosing the Office Simulation course is because this course is the basis for students to become familiar with administrative and administrative practices in the concept of office administration. This research is Research and Development (RnD) research using the ADDIE development model which consists of 5 (five) implementation stages, namely: (1) Analysis, (2) Design, (3) Development (4) Implementation, and (4) Evaluation. The data analysis techniques used in research include 3 (three) types, namely Validity, Effectiveness and Practicality. The results of this research show that the average percentage of validator scores for the content aspect is 88.66%, the presentation aspect is 90.66% and the language is 92.88%, these three aspects show that the office simulation book is very suitable for use. Meanwhile, practical testing for the content aspect was 93.04%, the presentation aspect was 88.05% and the language aspect was 88.04%. From this tabulation, the office simulation book is very practical to use. In testing effectiveness through parametric tests, a calculated t value of 26.599 can be obtained with a significance value of 0.00 < 0.05, so H0 is rejected. Thus, student learning outcomes after using office simulation books are significantly higher than those who do not use teaching materials. Keywords: Teaching Material, Learning Outcomes, Office Simulation